Zum Status eines mentalen Lexikons bei einem bilingualen Sprecher - Legutko-Marszalek, Iwona (Glottodidactica, 2006)
On status of mental lexicon of bilingual people. Bilingual people have learnt the second language in a directed way, in institutionalised conditions, achieving linguistic and communicative competence close to competences of the first language, in reception as well as production. Do these people haev a common mental lexicon or two different ones? The author’s research have shown that students posses two separate mental lexicons